Jawabanmu

2014-01-23T11:39:18+07:00
X + 3 = 0 ; x = - 3 => f (-3) = 11
x - 1 = 0 ; x = 1 => f (1) = - 5
menentukan sisa f(x)-nya :
s (x) = f (a) - f(b) (x) / a-b + a. f (b) - b.f (a) / a - b
        = 11 - (-5) (x) / -3 -1 + -3.-5 - 1. 11 / -3-1
        = 16x /- 4 + 4 /- 4
        = - 4x -1    








2014-01-23T13:30:29+07:00
F(-3)=11 dan f(1)= -5
f(x) = (x+3)(x-1) H(x) + px + q
f(-3) = 11⇔ -3p+q = 11
f(1) = 5⇔       p+q = -5    - 
                     -4p = 16 ⇔ p = -4 dan q =  -1
jadi sisanya -4x -1